An economic evaluation of the European Union's 2030 Climate Policy Plan - Thomas R. Sadler (Global Business & Finance Review (GBFR), 2023)
Purpose: The purpose of the study is to evaluate the European Union's "Fit for 55" plan, announced in 2021, which intends to meet a 2030 goal of reducing carbon emissions by 55 percent from 1990 levels. Design/methodology/approach: An analytical model is used to assess the impact of the EU environmental policies, including the carbon border tax, emissions trading system, energy efficiency, and emission standards. Findings: The study finds that the environmental policies achieve different policy criteria, including cost minimization, equalization of marginal abatement cost, minimization of general equilibrium cost, political feasibility, and minimization of inequitable impacts across income groups. But no single policy instrument is necessarily superior to the others. The paper finds that a revenue-neutral carbon border tax and an emissions trading system with auctioned permits satisfy the most evaluation criteria. Research limitations/implications: For the purpose of simplification, the model ignores dynamic extensions. That is, the adjustments of businesses to policy measures and the effects on emissions are beyond the scope of this analysis. Originality/value: The study develops a model that evaluates the European Union's environmental policies in a unifying perspective, assessing the tradeoffs of policy design.
Keywords: 650; Environmental Policy; Carbon Emissions; Climate Change